Closing Sexual Health Service Gaps With a New Service Model in Germany: Performance of an on-Site Integrated, Cross-Sectoral, Low Threshold Sexually Transmitted Infections/HIV Counseling and Treatment Service - Müller, Matthias C.; Usadel, Susanne; Zimmermann, Stefan; Fahrhöfer, Andreas; Kern, Winfried V.; Hoffmeister, Ulrike; Rieg, Siegbert (Frontiers in Public Health, 2022)
Purpose: In Germany, the incidence of bacterial sexual transmitted infections (STIs) is on the rise and still high for HIV infections. The Center for Sexual Health Freiburg (CSHF) was established offering low threshold access for STI/HIV counselling, testing, HIV pre-exposure prophylaxis (PrEP), and on-site treatment. Objective of this study was to analyse the performance of CSHF. Methods: Longitudinal study including all clients presenting between 1 May 2020 and 28 February 2021 at CSHF and willing to sign informed consent. Results: In the study period, 536 clients presented at CSHF of whom 417 clients were included in the study resulting in 668 client contacts. Clients’ median age was 28.1 years (range: 18.0-73.1), 55.9% were male, 42.0% female, 0.3% transman and 1.7% not binary. Clients’ sexual orientation was heterosexual (56.6%), homosexual men (26.2%) and bisexual (13.6%). STI screening resulted in detection of any STI in 3.4% (95% confidence interval (CI): 0.7-6.1) of women, in 3.1% (95% CI: 0.0-6.5) of heterosexual men, and in 22.2% (95% CI: 13.0-31.5) of men having sex with men (MSM) not taking PrEP. Eighty-one MSM received PrEP with a total follow-up of 57.3 person-years and 0.44 STI per person-year. Conclusion: The substantial burden of STI in the study population emphasizes the need for regular and low threshold STI screening services. The concept of CSHF may facilitate access to STI/HIV counselling, testing, and PrEP for a wide spectrum of people and may prove to be an important contribution to the efforts to reduce STI and HIV incidence in Germany.